Personalized Health Framework for Visually Impaired (Informatica, 2022)
Vision is one of the most essential human sense. The life of a visually impaired person can be transformed from a dependent individual to a productive and functional member of the society with the help of modern assistive technologies that use the concepts of deep learning and computer vision, the science that aims to mimic and automate human vision to provide a similar, if not better, capability to a computer.   However, the different solutions and technologies available today have limited outreach and end users cannot fully realize their benefits. This research work discusses an easily-operable and affordable android application designed to aid the visually impaired in healthcare management. It also aims to resolve the challenges faced due to visual impairment in daily life and uses the concepts of computer vision and deep learning. Broadly, the application consists of the following modules: object recognition in immediate surroundings using region-based convolutional neural networks, disease prediction with the help of symptoms, monitoring of health issues and voice assistant for in-app interaction and navigation.